Kualitas Pelayanan Di Kantor Lurah Simpang Baru Kecamatan Bina Widya Pekanbaru - Nining Maidawati; Sujianto Sujianto (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The needs and demands of society for improving the quality of service have shown that it is increasingly important for the government bureaucracy to respond, especially in the current era of globalization. To be able to respond to these changes, officials must truly have professional skills and have high discipline in facing various challenges towards improving service quality. The implication is that in entering an era of change, all functions and duties of the government as a public service can be carried out optimally, especially in providing services to the community, including government officials in Bina Widya District, Pekanbaru. Government organizations, service to the community is the main goal that cannot possibly be avoided because it is an obligation to provide services by creating the best service to the community, because it has become an obligation, the government should look for the best solutions to problems that are often faced, including obstacles to internships. namely originating from within the agency itself as well as external constraints that come from the community.